Effectiveness and Preparedness of Institutions' E-Learning Methods During the COVID-19 Pandemic for Residents' Medical Training in Saudi Arabia: A Pilot Study - Basim Alsaywid; Basim Alsaywid; Basim Alsaywid; Miltiadis D. Lytras; Miltiadis D. Lytras; Maha Abuzenada; Hara Lytra; Lama Sultan; Hala Badawoud; Wesam Abuznadah; Sami A. Alhaider; Abdulrahman Housawi; et al. (Frontiers Media S.A., 2021)
Background: Under the urgent circumstances of the COVID-19 pandemic, higher education institutions of an international scale have resorted to online education methods, exclusive or not. Among those, medical institutions are under double pressure, fighting the pandemic's effects and, at the same time providing efficient clinical training to their residents. The main aim of the study is to evaluate the preparedness of the educational institutions for the e-learning platform transition for the delivery of medical training and also to evaluate the overall satisfaction level of the participants with their e-learning experience.Methods: This is an observational cross-sectional study design. The survey's sample included 300 medical students and residents of multiple training levels and specialties, coming from more than 15 different cities of Saudi Arabia. Filling the questionnaire required specific inclusion criteria and all obtained data were secured by the Saudi Commission of Health specialty. The main objective was to evaluate the quality of e-learning methods provided by medical universities. For the collection of the data, Survey Monkey software was used and the analysis was conducted with SPSS.Results: The study found that the frequency of digital education use increased by ~61% during the coronavirus crisis, while almost 9 out of 10 residents have used some e-learning platform. It was reported that before the pandemic, participants' online training was deemed to be rather ineffective, given the rate of 3.65 out of 10. However, despite the increase in e-learning use after COVID-19, many obstacles arose duringcthe adaptation process. According to our survey: lectures and training sessions were not conducted as per the curriculum (56.33%); both students and instructors' academic behavior and attitude changed (48.33%); engagement, satisfaction, and motivation in class were rated low (5.93, 6.33, and 6.54 out of 10 accordingly), compared to the desired ones. Still, participants accredited e-learning as a potential mandatory tool (77.67%) and pinpointed the qualifications that in their opinion will maximize educational impact.Conclusion: The study concluded that innovative restructuring of online education should be based on defined critical success factors (technical support, content enhancement, pedagogy etc.) and if possible, set priority levels, so that a more permanent e-learning practice is achievable. Also our study confirmed that students were overall satisfied with the e-learning support of the training method.